An Examination Of The Relationship Between Inflation Rate And Stock Market Profitability Empirical Evidence From Tehran Stock Market - Ahmadi, Zahra (2009)
This study examines the relationship between Tehran Stock Exchange (TSE) profitability and inflation for the period from March 1998 to March 2008 by investigating the influences of inflation on three TSE's indices including TEDPIX as total index, INDUSDEX as price index for industrial companies, and TEDIX as dividends index. This research adopts two Vector Auto Regression (VAR) models. The first model contains consumer price index, gross domestic products, money supply, exchange rate, and interest rate as independent variables when the second model only considers consumer price index as independent variable.